AUTOMATIC DESIGNING OF POWER SUPPLY SYSTEMS - A. I. Kirspou; I. V. Kolosova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Development of automatic designing system for power supply of industrial enterprises is considered in the paper. Its complete structure and principle of operation are determined and established. Modern graphical interface and data scheme are developed, software is completely realized. Methodology and software correspond to the requirements of the up-to-date designing, describe a general algorithm of program process and also reveals properties of automatic designing system objects. Automatic designing system is based on module principle while using object-orientated programming. Automatic designing system makes it possible to carry out consistently designing calculations of power supply system and select the required equipment with subsequent output of all calculations in the form of explanatory note. Automatic designing system can be applied by designing organizations under conditions of actual designing.